Development of a quasi-dry electrode for EEG recording - Mota, A. R. (2013)
The present work reports on the development of a novel polymer-based electrode prototype for electroencephalography (EEG). The new electrode concept lies between the classic “wet” and “dry” electrodes, allowing addressing most of their drawbacks, while keeping the advantages of both. A localized skin hydration effect at the electrode/scalp contact point is achieved by the release of a small amount of a moisturizing agent (30 μl) from a reservoir inside the electrode, triggered by the electrode/scalp adduction. The electrode's functionality relies on the polymer mechanical properties and on the design of an electrode reservoir that deforms upon the application of a specified adduction force. Numerical modeling tools were used for the definition and analysis of the electrode geometry and the material mechanical properties. The new electrode prototype proved to be able to monitor EEG signals similar to those of the commercial silver/silver chloride electrodes by using a fraction of the hydrating solution necessary for the commercial electrodes, thus avoiding to damage or dirtying the patient's hair. Furthermore, due to the small amount of moisturizing agent employed, the risk of conductive bridges between adjacent electrodes due to gel running is considerably reduced.